High-dose versus low-dose tranexamic acid for paediatric craniosynostosis surgery: a double-blind randomised controlled non-inferiority trial. (September 2020) - Goobie, Susan M.; Staffa, Steven J.; Meara, John G.; Proctor, Mark R.; Tumolo, Miriam; Cangemi, Giuliana; Disma, Nicola
Abstract: Background: Tranexamic acid (TXA) reduces blood loss and transfusion in paediatric craniosynostosis surgery. The hypothesis is that low-dose TXA, determined by pharmacokinetic modelling, is non-inferior to high-dose TXA in decreasing blood loss and transfusion in children. Methods: Children undergoing craniosynostosis surgery were enrolled in a two-centre, prospective, double-blind, randomised, non-inferiority controlled trial to receive high TXA (50 mg kg −1 followed by 5 mg kg −1 h −1 ) or low TXA (10 mg kg −1 followed by 5 mg kg −1 h −1 ). Primary outcome was blood loss. Low dose was determined to be non-inferior to high dose if the 95% confidence interval (CI) for the mean difference in blood loss was above the non-inferiority margin of –20 ml kg −1 . Secondary outcomes were transfusion, TXA plasma concentrations, and biological markers of fibrinolysis and inflammation. Results: Sixty-eight children were included. Values were non-inferior regarding blood loss (39.4 [4.4] vs 40.3 [6.2] ml kg −1 [difference=0.9; 95% CI: –14.2, 15.9]) and blood transfusion (21.3 [1.6] vs 23.6 [1.5] ml kg −1 [difference=2.3; 95% CI: –2.1, 6.7]) between high-dose ( n =32) and low-dose ( n =34) groups, respectively. The TXA plasma concentrations during surgery averaged 50.2 (8.0) and 29.6 (7.6) μg ml −1 . There was no difference in fibrinolytic and inflammatory biological marker concentrations. No adverse events were observed. Conclusions: Tranexamic acid 10 mg kg −1 followed by 5 mg kg −1 h −1 is not less effective than a higher dose of 50 mg kg −1 and 5 mg kg −1 h −1 in reducing blood loss and transfusion in paediatric craniosynostosis surgery. Clinical trial registration: NCT02188576.